HUBUNGAN PENGETAHUAN, SIKAP DAN SARANA PRASARANA DENGAN PERILAKU MASYARAKAT DALAM PENERAPAN PROTOKOL KESEHATAN COVID-19 - Fitria, Rosa; Jumaini, Jumaini; Agrina, Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
COVID-19 cases in the world reached 21,700,823 confirmed by COVID-19. Out of the total cases in the world, 770,523 confirmed total deaths due to coronavirus and already 14,407,913 patients were declared cured. The purpose of this study is to know the relationship of knowledge, attitudes and infrastructure facilities with community behavior in the application of health protocols covid-19. The design of this study uses cross sectional studies. The large sample determined in this study was 400 respondents taken from 9 subdistricts of Tampan which consisted of the distribution of samples of each village. This research method uses descriptive analysis, which aims to systematically and factually describe the facts and relationships between variables investigated by collecting data, processing, analyzing, and interpreting data in statistical hypothesis testing. The results of this study showed the largest respondents were amongthe 26 - 35 years old with the number of 175 respondents (44%), the sex of the largest female respondents with the number of 255 respondents (64%), the marital status of unmarried respondents with the number of 204 respondents (51%), the last education respondents S1/2/3 with a total of 187 respondents (47%), the work of private employee respondents with a total of 155 respondents (39%), the level of good knowledge with the number of 173 respoden (43%), positive attitude with the number of 278 res (70%), good infrastructure with a total of 268 respoden (67%), positive behavior with a total of 209 respoden (52.%), no knowledge relationship with the behavior of respondents with a signification value of 0.304 (p> ;0.05), there is a relationship between attitude and behavior of respondents with a signification value of 0.001 (p < 0.05), there is a relationship between infrastructure facilities and the behavior of respondents with a signification value of 0.000 (p < 0.05 ). Keyword: Attitude, Behavior, Covid-19, Heath Protocol, Infrastrukture, Knowledge